Three ways of looking at morphological rivalry. (March 2023) - Aronoff, Mark
Abstract : Blocking and elsewhere distribution have been at the forefront of morphological theory for half a century. Each involves the preemption of one word by another. Neither is fundamental. A combination of Gause's Principle of Competitive Exclusion and Yang's Tolerance Principle, both devised for other reasons and both formalized mathematically, provides an explanatory basis for both blocking and elsewhere distribution.